2015
DOI: 10.1080/01402382.2014.993166
|View full text |Cite
|
Sign up to set email alerts
|

Ministerial Importance and Survival in Government: Tough at the Top?

Abstract: Are holders of important ministerial positions more likely to survive in cabinet than their colleagues who hold less important positions? This study examines the relationship between the importance of a ministerial position and the length of time ministers are able to survive in government. It is based on an original dataset of cabinet ministers in seven West European countries from 1945-2011. Employing a little-used measure of ministerial survival based on overall time in government, we find that holders of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
0
39
0
1
Order By: Relevance
“…The bulk of this work focuses on the determinants of minister selection and survival on a country-by-country basis (e.g., Bäck et al 2009;Berlinski, Dewan, and Dowding 2010;Fischer and Kaiser 2007;Kam et al 2010;Kerby 2011;Rodríguez-Teruel 2011;Smith and Martin 2017). Several previous studies employ cross-national data (e.g., Bright, Döring, and Little 2015;Huber and Martinez-Gallardo 2008), and data resources have been made publicly available for researchers interested in comparisons. The Selection and Deselection of Political Elites (SEDEPE) research network offers a dataset on 19 European countries from 1945 to 1984 (Dowding and Dumont 2009), while Alexiadou (2016) offers data on 18 OECD countries from 1945 to 2010, and Bértoa (2020) presents a new dataset on European democracies since 1848.…”
Section: Existing Datasetsmentioning
confidence: 99%
“…The bulk of this work focuses on the determinants of minister selection and survival on a country-by-country basis (e.g., Bäck et al 2009;Berlinski, Dewan, and Dowding 2010;Fischer and Kaiser 2007;Kam et al 2010;Kerby 2011;Rodríguez-Teruel 2011;Smith and Martin 2017). Several previous studies employ cross-national data (e.g., Bright, Döring, and Little 2015;Huber and Martinez-Gallardo 2008), and data resources have been made publicly available for researchers interested in comparisons. The Selection and Deselection of Political Elites (SEDEPE) research network offers a dataset on 19 European countries from 1945 to 1984 (Dowding and Dumont 2009), while Alexiadou (2016) offers data on 18 OECD countries from 1945 to 2010, and Bértoa (2020) presents a new dataset on European democracies since 1848.…”
Section: Existing Datasetsmentioning
confidence: 99%
“…4, 2020 Bäck et al 2011). Studies have also shown that portfolio salience affects ministerial duration (Hansen et al 2013;Bright et al 2015). Ministers with more salient portfolios last longer in cabinet than their colleagues.…”
Section: Studying Portfolio Saliencementioning
confidence: 99%
“…Therefore (Bright et al, 2015), Ministries focused on Welfare issues (such as the Ministry of Social Security or the Ministries of Work, Health or Educational Affairs) may tend to offer their incumbents a longer duration of political office. The reasons are related to the motivations of popularity that must be managed by the chiefs of government (Silva, 2015) combined with the importance of Welfare policies to most of the major parties of western economies (Druckman and Warwick, 2005).…”
Section: Ii11 -A Minister As a Trusted Principalmentioning
confidence: 99%